The Empty Ballot Movement as a Form of Protest Voting in the 2024 Brebes Regency Regional Election - Hermanto, Bambang; Khu, Stanley; Adi Pamungkas, Wahyu; Setiyawan, Wahyu Beny Mukti; Rakhmanto, Bambang (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
The phenomenon of the empty ballot in the 2024 Regional Head Election (Pilkada) of Brebes Regency attracted significant public attention after receiving 341,407 votes (40.4%), while voter turnout reached only 58.27%, the lowest participation rate in Central Java. This study aims to describe the Empty Ballot Movement as a form of protest voting by employing a qualitative method involving 15 informants, consisting of the movement's leader, community leaders, volunteers, and residents. The findings reveal that the movement emerged as a response to dissatisfaction with local democracy, driven by three main factors: the dominance of oligarchic politics that produced a single-candidate election through the consolidation of political party support; the perception that the sole candidate represented a political dynasty due to connections with former officials previously implicated in corruption cases; and the proposed IDR 13,000 shallot price policy, which was perceived as harmful to farmers. The Empty Ballot Movement successfully garnered public sympathy and became a symbol of protest voting against political practices regarded as undemocratic.